The sciences in Islamicate societies in context - Brentjes, Sonja, author.
1 online resource.
Keywords: "This Variorum volume reprints ten papers on contextual elements of the so-called ancient sciences in Islamicate societies between the thirteenth and the seventeenth centuries. They address four major themes: the ancient sciences in educational institutions; courtly patronage of science; the role of the astral and other sciences in the Mamluk sultanate; and narratives about knowledge. The main arguments are directed against the then dominant historiographical claims about the exclusion of the ancient sciences from the madrasa and cognate educational institutes, the suppression of philosophy and other ancient sciences in Damascus after 1229, the limited role of the new experts for timekeeping in the educational and professional exercise of this science, and the marginal impact of astrology under Mamluk rule. It is shown that the muwaqqits (timekeepers) were important teachers at madrasas and Sufi convents, that Mamluk officers sought out astrologers for counselling and that narratives about knowledge reveal important information about scholarly debates and beliefs. Colophons and dedications are used to prove that courtly patronage for the ancient sciences continued uninterrupted until the end of the seventeenth century. Furthermore, these papers refute the idea of a continued and strong conflict between the ancient and modern sciences, showing rather shifting alliances between various of them and their regrouping in the classifications of the entire disciplinary edifice. These papers are suited for graduate teaching in the history of science and the intellectual, cultural and social history of the Middle East and for all readers interested in the study of the contexts of the sciences"--